Recurrent Hydatidiform Mole: A Case Report of Five Consecutive Molar Pregnancies Complicated by Thyrotoxicosis and Review of Literature (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Hydatidiform mole (HM) is the most common form of Gestational Trophoblastic Disease (GTD). Recurrence of HM is extremely rare. Here we report the case report of a patient with five consecutive complete hydatidiform moles without any normal pregnancy. A 41-years old lady, was referred to Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh with H/O repeated molar pregnancies. Her first molar pregnancy was in 2005, second in 2006, third in 2007 & fourth in 2014. All the molar pregnancies were managed by suction evacuation at her base hospital. Following evacuation of 4th molar pregnancy at base hospital, she was referred to BSMMU for subsequent management. Regular follow-up was done using molar card. All the pregnancies were complete hydatidiform mole (CHM) and were confirmed clinically and sonographically. None of the molar pregnancies needed treatment with chemotherapy. During her fifth molar pregnancy she developed shortness of breath and palpitation. Diagnostic work up in our hospital confirmed complete molar pregnancy with thyrotoxicosis, for which she received b-blocker agent and after normalization of thyrotoxicosis, she underwent total abdominal hysterectomy on 11. 10. 18. Now she is on regular follow up by serum bhCG and has no complication.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 52-55